Aplikasi Metode Whole Chromosome Painting untuk Mendeteksi Aberasi Kromosom pada Tumor Padat - Budiyanti, Ecie; Suryani, Des; Pawitan, Jeanne Adiwinata (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2014)
In solid tumor, conventional cytogenetic method usualy fails to detect chromosomal aberation due to failure in obtaining good quality metaphases. Therefore, special technique is required to get the karyotype of solid tumors. Whole chromosome painting (WCP) is a method to paint the chromosomes using Fluorescence In Situ Hybridization (FISH) technique. Application of WCP, both using one and multiple colors (mFISH or SKY) or their modifications can be used to identify chromosomal aberrations, which are valuable in helping to attain a diagnosis, to determine the prognosis and management, and to predict the response to therapy. Key words: chromosomal aberation, FISH, solid tumor, whole chromosome painting.